KANDUNGAN KARBON DI PERKEBUNAN KELAPA SAWIT PADA LAHAN GAMBUT DI DESA BERUMBUNG BARU KECAMATAN DAYUN KABUPATEN SIAK PROVINSI RIAU - Ivan Purba; Madju Siagian; Maria Erna (Program Pascasarjana Universitas Riau, 2019)
This research was conducted from February - April 2019 using the survey method. Samples of undergrowth, litter and palm oil were taken from palm oil plantations on peatlands in Berumbung Baru Village, Dayun District, Siak Regency of Riau Province. Sample analysis was carried out at the Marine Chemistry Laboratory of the Faculty of Fisheries and Marine Sciences, Riau University and calculated using the ICRAFF formula and using the allometry equation. The results showed the highest average total carbon content in the undergrowth was found in plot III (0.47 tons / ha). The highest average total carbon content in litter is found in plot II (0.47 tons / ha). The highest average total carbon content in palm oil is found in plot III (68 tons / ha). The total carbon content in plot I was 24.91 tons / ha, the total carbon content in plot II was 44.22 tons / ha and the total carbon content in plot III (68.86 tons / ha). The value of carbon benefits at the study site is Rp. 18,904,630. Overall, the total carbon content in palm oil plantations on peatlands in Berumbung Baru Village, Dayun District, Siak Regency of Riau Province is influenced by the age of palm oil plants. The higher the age of palm oil plants, the higher the carbon content.